Test the intermediary role of the general electronic behavior of the Syrian consumer in the impact of the spoken word to decide the decision to buy mobile phones (Damascus University Journal for the economic and Political sciences, 2021)
The purpose of this research is to study the impact of the electronic spoken word in the decision to buy the Syrian consumer for mobile phones by testing the role of its electronic public behavior in that effect.The researcher followed the analytical descriptive method through quantitative analysis of how the spoken word affects the general electronic behavior of the Syrian consumer, which in turn affects the decision to buy that consumer. A questionnaire consisting of five main axes was designed in addition to personal information on the sample. The questionnaire was distributed to a suitable sample. 388 questionnaire was collected and analyzed using SPSS, V.18 for testing hypotheses. There is a difference between the general electronic behavior of the consumer and the other personal variables of the research sample. As well as the impact of the word spoken electronic in the general electronic behavior of the consumer, and finally the impact of the general electronic behavior of the consumer in the decision to buy mobile devices.The study recommended that the marketing companies for mobile phones at the agent level adopt an electronic marketing strategy based on the principles of retailing and targeting the consumer via electronic social links in a scientific manner. The company should adopt electronic software to analyze the spoken word electronicallyand know the distribution of its negative and positive components correctly. CRM software to improve the spoken word positively and thus build a positive direction and the decision to buy the consumer for mobile phones marketed.
Keywords: Electronic spoken word; general electronic behavior; electronic social links; perceived discipline; Mobile phones